Reconciling editorial independence and public accountability issues in Public Broadcasting Service - Guy Berger; Denis Jjuuko (Communicare)
A public broadcaster is pulled in two directions: There is the need to be accountable to the public, and the imperative to be editorially independent at the same time. The first implies parameters and control systems; the second points to the need for autonomy. This distinctive tension marks out a key difference between public and private broadcasting (through the public accountability component), and between public and government-controlled broadcasting (through the editorial independence proviso). Several dimensions can be identified in regard to assessing accountability and editorial independence, and also to the way that policy can work to integrate these two apparently contradictory imperatives. In 2004, the South African Broadcasting Corporation (SABC) was required in effect to mediate the complex challenges in this tension by formulating detailed editorial policies and systems. The significance of the SABC experience also extends to understanding the nature of policy more broadly